DINAMIKA BAHASA BALI DALAM PERKEMBANGAN KEBUDAYAAN BALI - I Made Suweta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Language and culture are an inseparable unity. Without language, it is impossible for culture to develop, likewise without culture, language will be useless because it is less beneficial for human life. There are two problems in this paper, namely: what is the nature of Balinese culture? and what are the dynamics of Balinese in the development of Balinese culture? In essence, Balinese culture and Balinese language are inseparable, so that efforts to develop Balinese culture cannot be separated from efforts to develop Balinese language. This is also because the dynamics of Balinese culture and Balinese language must be in tune. Balinese culture is a necessity without being supported by the development of the Balinese language. The dynamics of Balinese culture should be in line with and in line with the development of the Balinese language, both of which are dynamic towards a dynamic Balinese civilization in accordance with the development of society and the demands of the times. Balinese language is very dynamic in its development, not only as a means of communication, but also useful in various aspects of community life: social organization, science, tools, economy, religion, and the arts.